Understanding Philip Roth - Shipe, Matthew (Understanding contemporary American literature., 2022)
"Philip Roth (1933-2018) was one of the most prolific, prominent, and controversial writers of his generation. He was awarded a Pulitzer Prize, two National Book Awards, two National Book Critics Circle awards, three PEN/Faulkner awards, and many others; his work is the subject of Philip Roth Studies, a journal published by Purdue UP in cooperation with the Philip Roth Society since 2005; his novels are frequently taught in undergraduate literature courses. In Understanding Philip Roth, Matthew Shipe offers one of the first single-authored critical overviews of Roth's complete oeuvre, aimed at undergraduates and general readers of Roth's works. By emphasizing the connections between Roth's early and later work, Shipe aims to offer a more complete portrait of how Roth's fiction evolved over the course of his career and how it engaged its historical moment(s). Seven chapters cover Roth's biography and major themes (Jewish identity, male sexual desire, American exceptionalism) and his novels in thematic, roughly chronological groups (the first fifteen years; the Nathan Zuckerman novels, writing, and identity; the Kepesh trilogy and intersections between art, sex, and gender politics; Roth as a character in his own work; Roth's exploration of American history; later works and essays)"--